The Hitchcock Romance : Love and Irony in Hitchcock's Films. - Brill, Lesley (Princeton : Princeton University Press, 1988)
Was Alfred Hitchcock a cynical trifler with his audience's emotions, as he liked to pretend? Or was he a profoundly humane artist? Most commentators leave Hitchcock's self-assessment unquestioned, but this book shows that his movies convey an affectionate, hopeful understanding of human nature and the redemptive possibilities of love. Lesley Brill discusses Hitchcock's work as a whole and examines in detail twenty-two films, from perennial favorites like North by Northwest to neglected masterpieces like Rich and Strange.
Cover Page -- Half-title Page -- Title Page -- Copyright Page -- Dedication Page -- Contents -- Frame Enlargements -- Acknowledgments -- Introduction -- 1. North by Northwest and Romance -- 2. Young and Innocent: Comic Romances of False Accusation -- 3. Mixed Romances -- 4. Do Not Presume: Irony -- 5. ""I Look Up, I Look Down -- 6. Bygones be Bygones -- 7. ""Love's Not Time's Fool -- Index
Description based upon print version of record.
JSTOR
Keywords: Hitchcock, Alfred, -- 1899-1980 -- Criticism and interpretation; Hitchcock, Alfred, -- 1899-1980; Love in motion pictures; Irony in motion pictures; Amour au cinéma.; Ironie au cinéma.; Love in motion pictures; Irony in motion pictures; Criticism, interpretation, etc